Effectiveness Of Human Resource Management Practices In Improving Employee Satisfaction - Naufal lathif; Cantika Daryanti; Angga Pratama (Jurnal Intelek Insan Cendikia, 2026)
This study aims to analyze the effectiveness of human resource management (HRM) practices in improving employee satisfaction by identifying the role of competency-based recruitment, continuous training, objective performance management, fair compensation, and a supportive work environment. The method used is a Systematic Literature Review (SLR) by examining 20 journals indexed by Sinta, DOAJ, Google Scholar, and Scopus published in the period 2015–2025. Articles were selected based on topic suitability, methodological quality, and the availability of complete data. The results of the study indicate that effective HRM practices consistently have a positive effect on employee satisfaction, motivation, and performance. Structured training, transformational leadership, and a competitive compensation system have been proven to be dominant factors in increasing job satisfaction. In addition, job satisfaction acts as a strong mediating variable in the relationship between HRM practices and organizational performance. These findings confirm that holistic and sustainable HRM management is key to creating a productive, loyal, and high-performing workforce.